Delta peritoneal cancer index (ΔPCI): A new dynamic prognostic parameter for survival in patients with colorectal peritoneal metastases. Issue 4 (April 2020) - Hentzen, Judith E.K.R.; van der Plas, Willemijn Y.; Kuipers, Hendrien; Ramcharan, Swades; Been, Lukas B.; Hoogwater, Frederik J.H.; van Ginkel, Robert J.; van Dam, Gooitzen M.; Hemmer, Patrick H.J.; Kruijff, Schelto
Structured Abstract: Background: The peritoneal cancer index (PCI) calculated during exploratory laparotomy is a strong prognostic factor for overall survival (OS) in patients with colorectal peritoneal metastases (PM) who undergo cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS + HIPEC). Progression of the PCI between diagnostic laparoscopy (DLS) and potential CRS + HIPEC (ΔPCI) might be a more dynamic prognostic factor for OS after CRS + HIPEC. Materials and methods: Between 2012 and 2018, all colorectal PM patients who underwent an exploratory laparotomy for potential CRS + HIPEC after DLS were retrospectively identified from a prospectively maintained database. Patients were divided into stable disease (ΔPCI 0–3), mild progression (ΔPCI 4–9), or severe progression (ΔPCI ≥10). Kaplan–Meier analysis and a multivariate Cox regression were performed. Results: Eighty-four patients (ΔPCI 0–3, n  = 35; ΔPCI 4–9, n  = 34; and ΔPCI ≥10, n  = 15) were analysed. Median OS after CRS + HIPEC was significantly decreased in patients with a ΔPCI of 4–9 (35.1 [95% CI 25.5–44.6]) or ΔPCI ≥10 (24.1 [95% CI 11.7–36.5]) compared to patients with a ΔPCI of 0–3 (47.9 [95% CI 40.0–55.7], p  = 0.004). In multivariate regression analysis, ΔPCI remained an independent risk factor for OS: ΔPCI 4–9 HR 3.1 (95% CI 1.4–7.2, p  = 0.007) and ΔPCI ≥10 HR 4.4 (95% CI 1.5–13.1, p  = 0.007). Conclusion: A high ΔPCI is an independent dynamic prognostic factor for OS and might reflect a more aggressive tumour biology in patients with colorectal PM. HIPEC surgeons should be aware of a high-ΔPCI-associated diminished prognosis and should reconsider CRS + HIPEC when confronted with a ΔPCI ≥10.